PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS III SEKOLAH DASAR NEGERI 101 PEKANBARU - Rieska Nofieza Rizky; Otang Kurniaman; Lazim N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the low result in learning math by the students. The researcher assumes that one of it reason is the ability of teacher to deliver material is less interest of less able to stimulate students to react and give respond. The use of instructional media will be able to raise the motivation and stimulation of learning activities. One of learning media that can be used is the interactive media. Interactive media is learning media, that is a combination of sounds, images, text, animation and color. The media have made a different atmosphere in the learning-teaching process which is usually the subject matter taught in lectures, assignment and monotonous discussions. With this media will make students become interested, memorable and long term in the memory. This type of research is a quasi experimental study, with the study design non equivalent control group design. The research subject were the students in third - grade of elementary school 101 Pekanbaru. A third - grade students as a control class and B third – grade students as an experiment class. Collecting data were analyzed by using normality test, homogeneity test, t-test, gain, and correlation coefficients. Based on the analysis of data obtained interactive learning media influence on classroom experiments at 65,76 %. In the (t-test) average of differences of significance test on the index gain experiment class with control class earned 1,502 > table 1.666. it is that there are no significant differences in learning result between control and experiment classes. Therefore, from the hypothesis of this study there are the effect of the use of interactive learning media toward the result of learning math students’ in third – grade of elementary school 101 Pekanbaru.Key Words: interactive learning media, learning math result